Web2forDev: News for the rest of us - Elliott, Kim; Adams, Matt (Technical Centre for Agricultural and Rural Cooperation, 2007)
By drawing on web 2.0 tools to promote citizen journalism rabble.ca provides a template for others. This sneak preview into the relaunch of the popular news site shows that grassroots media has never been more accessible